Outsourcing Tenaga Kerja: Analisis terhadap Maslahat dan Mafsadat yang Ditimbulkan Menurut Hukum Islam - Arsad Nasution, Muhammad; Siregar, Rosnani (STAINI Press, 2025)
The outsourcing system in employment is a contemporary phenomenon that is not explicitly known in Islamic law. However, this system has similarities with the shirkah contract of abdan in the muamalah of Islam. The question that arises is how Islamic law responds to the practice of outsourcing and whether this system brings benefits to workers or actually causes mafsadat. This study aims to examine the impact of the outsourcing system on the welfare of workers through the maslahah approach, especially the concepts of istihsan and mashalih al-mursalah. This study uses a qualitative method based on literature review by analyzing data from various journals and related literature. The results of the study show that the outsourcing system causes more mafsadat than benefit. Outsourced workers often experience injustices, such as substandard wages, lack of benefits and social security, and weak legal protections due to unclear employment relationships between labor providers and service users. In addition, they are also limited in their right to unionize. In conclusion, the outsourcing system benefits companies more than workers. Therefore, from the perspective of Islamic law, this mechanism should be limited to training and recruitment providers, while workers placed in a company should be appointed as permanent employees.